The concept of state and governance in ancient history: Mesopotamia and ancient Egypt as a model - Tawfiq, Emad Tariq (Al-Adab Journal, 2019)
The aforementioned topic examines the study of state building in Mesopotamia and Pharaonic Egypt, from the stage of the city (the city) to the empire and through the development of the system of government, especially in Pharaonic Egypt.The general basis of government is the religious character of both civilizations, as well as the emergence of the city-state as a first stage in the ladder of building the complete state and then the empire as a final stage for the expansion of the state. Without a doubt, political titles have indicated the importance of that expansion as well as management as a complement to building the state.We can say that the cosmic state, led by the gods, was the model by which the residents of Mesopotamia and even the Pharaohs believed in building the earthly state, and it is self-evident that each civilization has its advantages and imprints in shaping the general framework of the state and citizenship. The research is divided into two parts, in the first we talked about the form of the state in Mesopotamia as a religious cosmic genesis from the gods and then delegated to human beings and the transition to ownership, while the other section included the study of the state in Pharaonic Egypt and its development and through it we get to know the concept of citizenship which is without doubt contrary to the concept Contemporary.The Egyptian political concept has evolved, especially after the involvement of women in government and state administration since the era of the second family and the involvement of children, especially the crown prince in the administration since the twelfth family age, as well as the priests ’assumption of affairs since the fifth family era, and their influence on the internal politics of the state, as well as the army that took over In the era of the eighteenth and nineteenth dynasties, in addition to the influence of the minister or Aziz of Egypt and his government as they represent the state and its pillars. At the conclusion of the research, the research reached a firm historical fact that the basis of the state is religious and its principle as well, the difference in particles and development according to the political conditions of both civilizations, as well as the political form of Mesopotamia remains unchanged unlike the Pharaonic Egypt.